Introduction to Chemicals from Biomass - Clark, James H. (Wiley, 2014)
the 1st edition: "Drawing on the expertise of the authors the book involves a degree of plant biology and chemical engineering, which illustrates the multidisciplinary nature of the topic beautifully" - Chemistry World
Description based on publisher supplied metadata and other sources
Keywords: Biomass chemicals; Organic compounds; Natürliche Ressourcen; Biomasse; Biomasseverarbeitung; Organische Verbindungen